2017
DOI: 10.1111/hsc.12414
|View full text |Cite
|
Sign up to set email alerts
|

Depression and discrimination in the lives of women, transgender and gender liminal people in Ontario, Canada

Abstract: This article uses an intersectionality lens to explore how experiences of race, gender, sexuality, class and their intersections are associated with depression and unmet need for mental healthcare in a population of 704 women and transgender/gender liminal people from Ontario, Canada. A survey collecting demographic information, information about mental health and use of mental healthcare services, and data for the Everyday Discrimination Scale and the PHQ-9 Questionnaire for Depression was completed by 704 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
1
18
0
1
Order By: Relevance
“…In addition to being denied these services and opportunities, which is also reported among transgender women in other countries [ 5 ], our study suggests that these discriminatory experiences significantly increase the odds of having depressive symptoms by 1.5 o 2.4 fold. Similar associations between stigma and discrimination victimization on one hand and depression on the other have also been reported in the United States and Canada [ 3 , 8 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition to being denied these services and opportunities, which is also reported among transgender women in other countries [ 5 ], our study suggests that these discriminatory experiences significantly increase the odds of having depressive symptoms by 1.5 o 2.4 fold. Similar associations between stigma and discrimination victimization on one hand and depression on the other have also been reported in the United States and Canada [ 3 , 8 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…More recently, researchers have started investigating the confluence of different forms of marginalization on the health and wellbeing of transgender women [ 8 ]. In Colombia, a recent study showed how the intersection of conflict, violence, homonegativity, and ‘social cleansing’ increase the vulnerability of displaced transgender women to HIV [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transgender suicide attempt rates, for example, are nine times the national average (45), often worst among transmasculine youth (46). Predictors of depression among transgender people, exacerbated by intersections of race, gender, class, and sexuality (47), include minority stress, low self-esteem, overt discrimination and victimization, lack of social support, and little or no access to medical transition technologies where desired (48)(49)(50). Given higher rates of depression and lower rates of physical activity (51), the study of curiosity within trans populations requires further study (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, transgender people are different from lesbians, gays, and bisexuals and might have different health and life experiences than gay and lesbians [ 20 ]. In light of the large numbers of transgender persons and the international efforts to endorse and strengthen human rights of neglected and marginalized groups, analysis of global research activity in transgender health becomes important [ 21 – 29 ]. Therefore, the aim of this study was to assess peer-reviewed literature in transgender health and present the results in bibliometric tables and maps.…”
Section: Introductionmentioning
confidence: 99%